Investigating the Role of Carpet Production in the Economic and Social Situation of Rural Households in Aq Qala Township - Bahman Sahneh; Mohammad Amin Khorasani (Pizhūhish/hā-yi Rūstāyī, 2021)
Production of Turkmen handmade carpet is one of the important activities outside farms and it is the source of income for lots of rural families. The objective of this survey is to do an analysis of the effect of handmade carpet production on the improvement of the sustainable livelihood of rural families in Aq Qala. This is an applied survey that uses descriptive-analytical method. Its statistical population is the families residing in 10 villages around the city of Aq Qala. The sample size was selected by Cochrane’s formula and includes 367 families with women working in the production of handmade carpets. In order to study economic and social indexes, 33 variables were used in the form of Likert’s scale. Data collection tools were researcher-made questionnaires whose content validity was approved by university professors; their reliability for economic variables was obtained 82% and for social variables 91%. In order to analyze the data, Chi-square correlation analysis, and Freidman and Kruskal Wallis mean value comparison were used in SPSS software, and for preparing a map, ArcGIS software was used. The results achieved from correlation analysis of the studied factors show that there is a 99% significant relationship between the level of education and economic and social factors. Also, Kruskal Wallis test results show no special difference between the studied villages except the increase of saving, and the effect of handmade carpet production is equal in all villages. The most important challenges are the unpredictability of raw material prices, problems related to financial support, production and sometimes the supply of non-standard products.